On local strength analysis in critical conditions of mooring and towing for a chemical tanker - Paul-Adrian Pascu; Leonard Domnișoru; Eugen Gavan (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding)
Mooring and towing equipments ensure stability, control and safety in stationary (mooring) and transit (towing) situations. Mooring equipment is responsible for securing a vessel in place at a dock, pier, or offshore structure. Proper mooring equipment and reinforcements ensure that the vessel remains safely secured despite the influence of environmental loads. Towing equipment is essential for moving ship over short or long distances, either due to mechanical failures of the vessel or to relocate it. Towing is especially critical in rescue operations. The study involves a chemical tanker detailed strength check at mooring (at pier) and towing (on relocation) cases. In both cases the worst scenario was taken into consideration.